2017
DOI: 10.1016/j.chroma.2017.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterisation of aerosols emitted by electronic cigarettes using thermal desorption–gas chromatography–time of flight mass spectrometry

Abstract: A non-targeted analytical method, using thermal desorption-gas chromatography-time of flight mass spectrometry, to detect, identify and semi-quantify volatile and semi-volatile organic constituents of e-cigarette aerosols is presented. A heart-cutting process with a Deans Switch has been applied to avoid saturation of the mass analyser by high-abundance bulk components. Between 30 and 90 compounds were detected in four aerosol samples generated by e-cigarettes, depending on the added flavourings. The method an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 16 publications
0
59
0
Order By: Relevance
“…Studies of vape liquids consistently confi rm the presence of toxic substances in the resulting vape aerosol. [37][38][39][40] Depending on the combination of fl avorings and solvents in a given e-liquid, a variety of chemicals can be detected in the aerosol from various vaping devices. Chemicals that may be detected include known irritants of respiratory mucosa, as well as various carcinogens.…”
Section: ■ Bad Things In E-liquid Aerosolmentioning
confidence: 99%
“…Studies of vape liquids consistently confi rm the presence of toxic substances in the resulting vape aerosol. [37][38][39][40] Depending on the combination of fl avorings and solvents in a given e-liquid, a variety of chemicals can be detected in the aerosol from various vaping devices. Chemicals that may be detected include known irritants of respiratory mucosa, as well as various carcinogens.…”
Section: ■ Bad Things In E-liquid Aerosolmentioning
confidence: 99%
“…As previously indicated, in addition to nicotine, ENDS usage exposes the user, including the developing conceptus, to constituents of the aerosol generated from vaporization of the base e-liquid. These include known carcinogens and toxic chemicals such as nitrosamines, formaldehyde, acetaldehyde, acrolein, propylene glycol, glycerin and the heavy metals lead, chromium, manganese and nickel (Geiss, Bianchi, Barahona, & Barrero-Moreno, 2015;Goniewicz et al, 2014;Hess, Olmedo, Navas-Acien, et al, 2017;Logue, Sleiman, Montesinos, et al, 2017;Olmedo et al, 2018;Rawlinson, Martin, Frosina, & Wright, 2017;Sleiman, Logue, Montesinos, et al, 2016;Williams, Villarreal, Bozhilov, Lin, & Talbot, 2013), all toxic when inhaled. The apparent source of many of the heavy metals is leakage from the e-cigarette heating coils into the aerosols that users inhale (Olmedo et al, 2018).…”
Section: Are Ends a "Safer Alternative" To Tobacco Smoking During Pmentioning
confidence: 99%
“…12,13 Many of the toxicants in tobacco smoke are simply not present in e-cigarette aerosols at detectable levels when assessed using machinebased aerosol generation or are at levels equivalent to the tolerances allowed in medicinal products. [11][12][13][14][15][16][17][18][19] A recent review of chemical, toxicological, and clinical studies for both e-cigarette liquids and aerosols indicated that they contain reduced levels of harmful chemicals and emissions, induced significantly less cytotoxicity, and resulted in fewer cardiovascular and respiratory functional effects when compared with reported data on tobacco cigarettes. 1 Romagna et al reported e-cigarette aerosol to be significantly less cytotoxic than tobacco smoke in fibroblasts, 20 and Farsalinos et al concluded the same findings in myocardial cells.…”
Section: Introductionmentioning
confidence: 99%